Religious Belief-Related Factors Enhance the Impact of Soundscapes in Han Chinese Buddhist Temples on Mental Health - Zhang, Dongxu; Kong, Chunxiao; Zhang, Mei; Kang, Jian (Frontiers in Psychology, 2022)
In contemporary society, mental health issues have received increasing attention. Moreover, how people perceive the acoustic environment affects mental health. In religious places, the unique religious soundscape, composed of the acoustic environment and sounds, has an obvious effect on mental health. In China, Han Chinese Buddhism has a long history and is currently the religion with the largest number of believers. The soundscape of temples has always been an important component of creating a Buddhist atmosphere. For this study, questionnaires were distributed to believers and tourists inside and outside several well-known Han Chinese Buddhist temples in China to analyse the relationship between evaluations of temple soundscapes (including the overall acoustic environment and preferences for typical sounds) and mental health and the role of religious belief-related factors in this relationship. The results indicated that for the respondents, the overall acoustic environment of Buddhist temples was significantly correlated with mental health and that preference for three sounds in Buddhist temples, i.e., bells, wind chimes and chanting sounds, were significantly correlated with mental health. Among religious belief-related factors, the attitude toward Buddhist thoughts, frequency of temple visitation and purpose for visiting temples can affect the correlation between the personal evaluations of temple soundscapes and mental health. For people who partially believe in Buddhist thoughts, who visit Buddhist temples twice or less per year, or who visit temples for tourism purposes, the correlations between evaluations of the overall acoustic environment and mental health are higher than for people without these religious characteristics. For people who fully believe in Buddhist thoughts or who visit temples neither to worship Buddha nor for tourism purposes, the correlations between the preferences for bells and wind chimes and mental health are higher than for people without these religious characteristics. For people who partially believe in Buddhist thoughts, the correlation between the preference for chanting and mental health is higher than for people with other attitudes toward Buddhist thoughts.